Responses of electrical properties of tea leaves to low-temperature stress - Yongzong, Lu; Yongguang, Hu; Xiliang, Zhang; Pingping, Li (International Journal of Agricultural and Biological Engineering, 2015)
Critical temperature is one of the most important parameters for the control of crop frost protection through airflow disturbance. It changes with complex weather conditions, thus it is difficult to be determined. A method of testing electrical property of tea leaves under cold stress was put forward to indicate critical temperature. The testing system was established to measure the capacitance, impedance, resistance and reactance of the samples under different air temperatures, air humidities and airflow velocities. The variation of the electrical property was also analyzed. The results show that at humidity below 70% and airflow velocity of 0 m/s the impedance and resistance increased slowly, while the reactance kept steady when air temperature decreased from 8.0°C to around −6.3°C, and then increased rapidly from around −6.3°C to −15.0°C. There were no significant differences of the above parameters and variation trend under different airflow velocities. There was an exponential relationship between the impedance and the temperature. The capacitance was rather small and almost no change occurred with air temperature under different conditions of air velocity and humidity, except a few abrupt peaks. The maximum peak capacitance was representative of its response at certain humidity and airflow velocity. The typical temperatures were close to a range, where the other three parameters began to increase rapidly. The typical temperature dropped to the lowest of −7.8°C at the airflow velocity of 0 m/s. Therefore, the characteristic response of the capacitance could indicate critical temperature of tea leaves.Keywords: low-temperature stress, electrical property, capacitance, Camellia Sinensis, critical temperatureDOI: 10.3965/j.ijabe.20150805.1426Citation: Lu Y Z, Hu Y G, Zhang X L, Li P P. Responses of electrical properties of tea leaves to low-temperature stress. Int J Agric & Biol Eng, 2015; 8(5): 170－175.